Analisis Penerapan Akuntansi Zakat pada Bank Umum Syariah di Indonesia Periode Tahun 2018 – 2020 - Muhammad Azuli Rizki; Efa Yonnedi; Vima Tista Putriana (Universitas Batanghari Jambi, 2023)
The company's zakat is a part of the company's annual report instrument. This study aims to determine the accounts that are components of the mandatory zakat and the company's zakat calculation methods. The subject of this research is aimed at 14 Islamic commercial banks in Indonesia by collecting annual report data on each Islamic commercial bank. The content analysis method is used to determine the accounts that are components of the object subject to corporate zakat in each Islamic commercial bank. 8 methods of calculating corporate zakat are the basis for analyzing potential zakat data contained in the annual report as an effort to determine the method of calculating corporate zakat in Islamic commercial banks. The results of this study reveal that 6 out of 14 Islamic commercial banks issue corporate zakat as muzzaki. The accounts used by Islamic commercial banks in Indonesia as objects of zakat are net income before tax at Bank Mandiri Syariah, Bank Mega Syariah, and Bank Panin Dubai Syariah with the calculation method multiplied by 2.5% according to the calculation method of Syarikat Takaful Malaysia Sdn Berhand. Furthermore, 3 other Islamic commercial banks, namely Bank Muamalat Indonesia, BNI Syariah, and BRI Syariah, use a net profit after tax account with the calculation multiplied by 2.5% according to the calculation method of Bank Muamalat Indonesia. Policies regarding the obligation to pay zakat should receive more attention so that companies have awareness as muzzaki. The method of calculating zakat in Indonesia should already have clear regulations in accordance with Islamic law so that there are not many differences in zakat by companies, especially Islamic commercial banks.